Will the spectrum of lesions prompting a “B3” breast core biopsy increase the benign biopsy rate? - Carder, P J (Copyright 2003 Journal of Clinical Pathology, 2003)
Aim: To audit the benign surgical biopsies in women screened, assessed, and referred by the Leeds/Wakefield Breast Screening Unit for the year 1999–2000 with a view to determining any association with a preoperative B3 core biopsy categorisation. Methods: The results of all preoperative diagnostic procedures in all patients who underwent surgical excision for a lesion proving benign in the year 1999–2000 were reviewed. Cases were categorised according to whether the preoperative fine needle aspirate cytology (FNAC) or core biopsy had been equivocal or of uncertain malignant potential (C3/B3), inadequate or unrepresentative (C1/B1), or benign (C2/B2). In those cases with a C3/B3 FNAC or core biopsy result, reasons for the uncertainty were determined by examination of the report and, where necessary, slides. In cases with C1/B1 or C2/B2 investigations and in those without a preoperative procedure, the reasons for surgical referral were determined from the screening records. Case records of all patients with a B3 core biopsy categorisation who subsequently proved to have malignancy were also reviewed. Results: Thirty six women had benign surgical biopsies in the 1999–2000 screening year. In 13 of the 36 patients, referral for diagnostic biopsy rested on radiological and/or pathological suspicion of radial scar. The core biopsy category was B3 in all but one, which was in the B1 category. In a further 10 patients, referral was based primarily on a pathological B3 categorisation. The reasons for this were as follows: papillary lesion (two), fibroepithelial lesion (two), atypical intraductal epithelial proliferation (two), stromal mucin (two), atypical lobular hyperplasia (one), and an unusual vascular lesion (one). Two cases with a C3 on FNAC also derived from papillary lesions. In the remaining nine patients, the radiological features were sufficiently suspicious to prompt referral in the presence of either inadequate/unrepresentative (C1/B1) or benign (B2) preoperative pathological findings. Two women had no preoperative needle biopsy. Conclusions: In 22 of 36 benign biopsies, the initial core biopsy categorisation was B3. According to the current system of core biopsy categorisation, a diversity of lesions must be designated as of “uncertain malignant potential” (B3) because the technique provides insufficient tissue for full histological assessment. The use of this category may increase the number of benign biopsies if all such cases are referred for surgery. An increase in the benign biopsy rate may be averted if larger amounts of tissue can be obtained using newer vacuum assisted techniques such as the Mammotome.